Assessment of treatability of the Tietê River through a process of coagulation-flocculation associated with hydrodynamic cavitation and ozonation - Campos, Valquíria [UNESP]; Domingos, Janaina M. F.; Nolasco, Marcelo A.; DE MORAIS, Leandro C. [UNESP]; Marques, Diego G. [UNESP] (FapUNIFESP (SciELO), 2024)
As it flows through the city of São Paulo, the Tietê River receives heavy discharges of industrial effluents and domestic sewage, resulting from the city’s continuous urban expansion and the inadequacy of its sanitary sewage system. This study focused on an analysis of the efficiency of PGα21Ca and quaternary ammonium tannate, water purification products, based on coagulation-flocculation and sedimentation tests, followed by treatment with a hydrodynamic cavitation reactor associated with ozonation in the treatment of Tietê River water. The removal of turbidity, apparent color, and chemical oxygen demand (COD) were evaluated. Jar testing assays were conducted, and the best turbidity removal rates were obtained with a concentration of 300 mg L-1 for PGα21Ca and 150 mg L-1 for quaternary ammonium tannate. The coagulation-flocculation treatment removed approximately 93% of turbidity for both coagulants. After combining coagulation-flocculation with hydrodynamic cavitation with ozonation, the final COD removal rate applying PGα21Ca was 47.63% in 1 hour of reaction, while that of quaternary ammonium tannate was 40.13% in 2 hours of reaction. Although the results appear to indicate the superior performance of PGα21Ca, it should be noted that the treatment with quaternary ammonium tannate also provided good results in reducing turbidity, COD, and apparent color, using a smaller dose of this coagulant and that its use may be more advantageous from an environmental point of view, due to its natural composition.
Keywords: coagulation-flocculation tests; hydrodynamic cavitation; ozonation; quaternary ammonium tannate; urban river; γ-polyglutamic acid